Which work characteristics predict employee outcomes for the public-sector employee? An examination of generic and occupation-specific characteristics - Noblet, A.; Teo, Stephen; McWilliams, J.; Rodwell, J. (Routledge, 2005)
The wide-ranging changes that have occurred in the public sector over recent years have placed increasing demands on public-sector employees. A survey of employees within a relatively commercially-oriented public-sector organization in Australia was used to test a demand-oriented generic model of employee well-being and a variety of situation-specific variables. The presence of support at work and the amount of control an employee had over their job were found to be key predictors of employee-level outcomes. Perceptions of pay and the perception of a lack of human resources (HR) were also found to predict employee outcome variables. The results emphasize the impact that middle managers and HR managers can have in terms of reducing the detrimental employee effects that can be caused by the introduction of new public management (NPM) and the potential for a positive impact on employees. In particular, public-sector managers can use the design of jobs and the development of social support mechanisms, such as employee assistance programmes, to maintain, if not improve, the quality of working life experienced by their employees. More broadly, this study has found that the job strain model is a useful tool in a public-sector environment and is likely to be of increasing utility with the continuing introduction or consolidation of NPM over time. Managing these issues in the new public sector could be a key means of protecting the key resource of the Australian public sector – the employees.